Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Essays on Cooperation in Differential Games - Hoof, Simon

Mechanisms, Preferences, and Heterogeneity in Matching Markets - Stroh-Maraun, Nadja

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.

Introduction to the Special Issue “Bargaining” - Haake, Claus-Jochen; Trockel, Walter (Homo Oeconomicus)
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Zuordnungsverfahren für Tauschbörsen - N., N.

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.

Kulturelle Unterschiede beim Lösen von Verhandlungsproblemen - N., N.

Productivity optimization through project matching - N., N.

Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

The Decomposability of the Nash Bargaining Solution in Labor Markets - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya
In this paper, we analyze the two-dimensional Nash bargaining solution (NBS) deploying a standard labor market negotiations model (see McDonald and Solow, 1981; Creedy and McDonald, 1991). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems such that the (Cartesian) product of the solutions of these problems replicates the solution of the two-dimensional problem, if the NBS is applied. However, this decomposition fails for any solution concept that does not satisfy the axiom of Independence of Irrelevant Alternatives (IIA axiom). Our decomposition result has significant implications for actual negotiations, as it allows for the decomposition of a multi-issue bargaining problem into a set of simpler problems, in particular a set of single-issue bargaining problems. In this way, the decomposition may help facilitate negotiations in labor markets and also in other environments.
Keywords: Labor market negotiations; Efficient bargains; Nash bargaining solution; Sequential bargaining; Restricted bargaining games

Duality for General TU-games Redefined - Aslan, Fatma; Duman, Papatya; Trockel, Walter
We criticize some conceptual weaknesses in the recent literature on coalitional TUgames and propose, based on our critics, a new definition of dual TU-games that coincides with the one in the literature on the class of super-additive games. We justify our new definition in four alternative ways: 1. Via an adequate definition of ecient payo vectors. 2. Via a modification of the Bondareva-Shapley duality. 3. Via an explicit consideration of \coalition building". 4. Via associating general TU-games to coalition-production economies. Rather than imputations, we base our analysis on a modification of aspirations.
Keywords: TU-games; duality; core; c-Core; cohesive games; complete game efficiency

Intermediaries in Networks - N., N.

Logrolling-Prozess: Theorie und formale Darstellung einer verhandlungsunterstützenden Methode - N., N.

Stability in two-sided matchings with asymmetric information - N., N.

Sincere and Sophisticated Players in Matching Markets - N., N.

Mechanismen zur Informationsgewinnung in Verhandlungen - N., N.

Die faire Verteilung unteilbarer Güter - N., N.

Axiomatisierungen des Banzhaf-Wertes - N., N.

Compatibilities in Matching Mechanisms - N., N.

Faire Aufteilung von unteilbaren Gütern: Untersuchung von Algorithmen auf Effizienz und Neidfreiheit - N., N.

Anwendung und Vergleich von Verhandlungslösungen auf das Netzwerk-Design-Problem - N., N.

Verhandlungen mit Intermediären in IT-Märkten: eine spieltheoretische Analyse - N., N.

A bargaining model for relative profit and market share delegation contracts - N., N.

Wettbewerb in Märkten für Dienstleitungen mit uninformierten Kunden - N., N.

Der Shapley-Wert als Index für phylogenetische Diversität - N., N.

Student's school matching mechanisms in the US - N., N.

Disaggregating User Evaluations Using the Shapley Value - Feldotto, Matthias; Haake, Claus-Jochen; Skopalik, Alexander; Stroh-Maraun, Nadja (Proceedings of the 13th Workshop on Economics of Networks, Systems and Computation (NetEcon 2018))
We consider a market where final products or services are compositions of a number of basic services. Users are asked to evaluate the quality of the composed product after purchase. The quality of the basic service influences the performance of the composed services but cannot be observed directly. The question we pose is whether it is possible to use user evaluations on composed services to assess the quality of basic services. We discuss how to combine aggregation of evaluations across users and disaggregation of information on composed services to derive valuations for the single components. As a solution we propose to use the (weighted) average as aggregation device in connection with the Shapley value as disaggregation method, since this combination fulfills natural requirements in our context. In addition, we address some occurring computational issues: We give an approximate solution concept using only a limited number of evaluations which guarantees nearly optimal results with reduced running time. Lastly, we show that a slightly modified Shapley value and the weighted average are still applicable if the evaluation profiles are incomplete.

Feedback Pareto weights in cooperative NTU differential games - Hoof, Simon
This note deals with agreeability in nontransferable utility (NTU) differential games. We introduce state feedback Pareto weights to enrich the set of efficient cooperative solutions. The framework is particularly useful if constant weights fail to support agreeability, but cooperation is desired nonetheless. The concept is applied to an adverting differential game.
Keywords: NTU differential games; variable Pareto weights; agreeability

Outcome Equivalence in School Choice with Reciprocal Preferences - Haake, Claus-Jochen; Stroh-Maraun, Nadja (Economics Letters)
We show that the Boston school choice mechanism (BM), the student proposing deferred acceptance algorithm (DA) and the top trading cycles algorithm (TTC) generate the same outcome when the colleges’ priorities are modified according to students’ preferences in a “first preferences first” manner. This outcome coincides with the BM outcome under original priorities. As a result, the DA and TTC mechanism that are non-manipulable under original priorities become vulnerable to strategic behavior.

Dynamic Voluntary Provision of Public Goods: The Recursive Nash Bargaining Solution - Hoof, Simon (Static & Dynamic Game Theory: Foundations & Applications)

On unification of solutions to the bargaining problem - Haake, Claus-Jochen; Qin, Cheng-Zhong
We establish axioms under which a bargaining solution can be found by the maximization of the CES function and is unique up to specification of the distribution and elasticity parameters. This solution is referred to as the CES solution which includes the NASH and egalitarian solutions as special cases. Next, we consider a normalization of the CES function and establish axioms, under which a bargaining solution can be found by the maximization of the normalized CES and is unique up to the specifications of the distribution and its substitution parameters. We refer to this solution as the normalized CES solution, which includes the Nash and Kalai-Smorodinsky solutions as special cases. Our paper contributes to bargaining theory by establishing unified characterizations of existing as well as a great variety of new bargaining solutions.
Keywords: Bargaining problem; CES Function; Normalized CES Function; Nash solution; Kalai-Smorodinsky Solution; Egalitarian Solution.

Thoughts on Social Design - Trockel, Walter; Haake, Claus-Jochen (Studies in Economic Design)
One of the fundamental problems in applications of methods and results from mechanism design and implementation theory is the effective enforcement of theoretically established equilibria by which social choice rules are implemented. Hurwicz (2008) and Myerson (2009) introduce different concepts of formalizing enforcement of institutional rules via the introduction of legal and illegal games. In this note the relation of their concepts with that of a social system defined inDebreu (1952) is analyzed and its potential of being instrumental for modelling institution design is discussed. The existence proof for such a system, also known as generalized game or abstract economy had been the basis for the existence proof of a competitive equilibrium of an economy.

Reduzierung des Energieverlustes im Smart Grid mittels Koalitionsbildung - Koch, Alexander

The Generalized Nash Bargaining Solution for Transfer Price Negotiations under Incomplete Information - Haake, Claus-Jochen; Recker, Sonja (Group Decision and Negotiation)
In our model two divisions negotiate over type-dependent contracts to determine an intrafirm transfer price for an intermediate product. Since the upstream division's (seller's) costs and downstream division's (buyer's) revenues are supposed to be private information, we formally consider cooperative bargaining problems under incomplete information. This means that the two divisions consider allocations of expected utility generated by mechanisms that satisfy (interim) individual rationality, incentive compatibility and/or ex post efficiency. Assuming two possible types for buyer and seller each, we first establish that the bargaining problem is regular, regardless whether or not incentive and/or efficiency constraints are imposed. This allows us to apply the generalized Nash bargaining solution to determine fair transfer payments and transfer quantities. In particular, the generalized Nash bargaining solution tries to balance divisional profits, while incentive constraints are still in place. In that sense a fair profit division is generated. Furthermore, by means of illustrative examples we derive general properties of this solution for the transfer pricing problem and compare the model developed here with the models existing in the literature. We demonstrate that there is a tradeoff between ex post efficiency and fairness.

Maintaining vs. Milking Good Reputation when Customer Feedback is Inaccurate - Mir Djawadi, Behnud; Fahr, Rene; Haake, Claus-Jochen; Recker, Sonja (PLoS ONE)
In Internet transactions, customers and service providers often interact once and anonymously. To prevent deceptive behavior a reputation system is particularly important to reduce information asymmetries about the quality of the offered product or service. In this study we examine the effectiveness of a reputation system to reduce information asymmetries when customers may make mistakes in judging the provided service quality. In our model, a service provider makes strategic quality choices and short-lived customers are asked to evaluate the observed quality by providing ratings to a reputation system. The customer is not able to always evaluate the service quality correctly and possibly submits an erroneous rating according to a predefined probability. Considering reputation profiles of the last three sales, within the theoretical model we derive that the service provider’s dichotomous quality decisions are independent of the reputation profile and depend only on the probabilities of receiving positive and negative ratings when providing low or high quality. Thus, a service provider optimally either maintains a good reputation or completely refrains from any reputation building process. However, when mapping our theoretical model to an experimental design we find that a significant share of subjects in the role of the service provider deviates from optimal behavior and chooses actions which are conditional on the current reputation profile. With respect to these individual quality choices we see that subjects use milking strategies which means that they exploit a good reputation. In particular, if the sales price is high, low quality is delivered until the price drops below a certain threshold, and then high quality is chosen until the price increases again.

More than skills: A novel matching proposal for multiplayer video games - Stroh-Maraun, Nadja; Kaimann, Daniel; Cox, Joe (Entertainment Computing)

A Duration Model Analysis of Consumer Preferences and Determinants of Video Game Consumption - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Journal of Consumer Behaviour)

A Note on Manipulability in School Choice with Reciprocal Preferences - Haake, Claus-Jochen; Stroh-Maraun, Nadja
We show that the Boston school choice mechanism (BM), the student proposing deferred acceptance algorithm (DA) and the top trading cycles algorithm (TTC) generate the same outcome when the colleges’ priorities are modified according to students’ preferences in a “first preferences first” manner. This outcome coincides with the BM outcome under original priorities. As a result, the DA and TTC mechanism that are non-manipulable under original priorities become vulnerable to strategic behavior.

Does Informational Equivalence Preserve Strategic Behavior? An Experimental Study on Trockel's Game - Duman, Papatya
The purpose of the present study is to experimentally test a version of the classical Chain Store Game (CSG) paradox, proposed by Trockel (1986), and determine whether one of the two theories of Induction and Deterrence, which were originally tested competitively by Selten (1978), may better account for the results. With complete and perfect information, the CSG of Selten (1978) was designed to analyze the role of reputation in repeated market interactions. Its results were discussed in two diﬀerent ways: one is based on backward induction, and the other is intuitively derived from a deterrence argument. As the two explanations are incompatible, alternative models have been proposed to understand them better. The alternative game proposed by Trockel is an imperfect information version of the CSG in which the order of the two players is changed in each round and the ’Out-Aggressive’ equilibrium is used to build reputation. The existence of more than one equilibrium is the basis for the building of reputation. To the best of my knowledge, this study is the ﬁrst attempt to experimentally test this alternative game with the same purpose.
Keywords: Chain Store Game; reputation building; entry deterrence; Trockel's game

Variety in the video game industry: An empirical study of the Wundt curve - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Managerial and Decision Economics)

Upstream Horizontal Mergers: Contractual Design under Bargaining in Vertically Related Industries - N, N

Bestimmung von Transferpreisen in vertikal integrierten Supply Chains - N, N

School-Choice Mechanismen im Vergleich Effizienz und Schwachstellen anhand von Beispielen aus Theorie und Praxis - N, N

Auswirkungen asymmetrischer Information auf Produktqualität - Reputationssysteme als Lösungsansatz - N, N

Automated Bilateral Multiple-issue negotiation with no information about opponent - N, N

Spieltheoretischer Verhandlungsansatz in der Sozialwahltheorie - N, N

Anreize in Bewertungssysteme - N, N

Facility Location Selection: How to select the optimal facility location ? - The Analytical Hierarchy Process - N, N

Wie werden elektronische Verhandlungen durch Präferenzen beeinflusst? - N, N

Bitcoins disruptives Potenzial im elektronischem Zahlungsverkehr - N, N

Diskriminierung in sozialen Netzwerken durch Versionierung - N, N

School Choice in Theory - N, N

Punktesystem für Zuwanderung in Deutschland nach Vorbild von Kanada - N, N

Agenda setting in jury decision by sequential majority voting - N, N

Verbindung Terrorismusforschung und Spieltheorie - N, N

Constitutions and groups - Mauleon, Ana; Roehl, Nils; Vannetelbosch, Vincent (Games and Economic Behavior)

Outsourcing und Qualität im Supply Chain - Eine Gleichgewichtsanalyse - Kühn, Sarah

Crowdfunding Plattformen als Vermittler auf zweiseitigen Märkten - Eine mikroökonomische Analyse - Gunning, Justine

How to adequately relocate asylum applicants within the European Union - An attempt to apply matching theory in the current migration crisis - Streck, Thomas

Asymmetric Dominance Effect with Multiple Decoys for Low- and High-Variance Lotteries - Sürücü, Oktay; Mir Djawadi, Behnud; Brangewitz, Sonja

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Multi-Dimensional Bargaining Problem and Nash Solution - A procedural approach - N, N

Game Theory solutions for the Transshipment Problem in Logistic Networks - N, N

Bitcoin, Ethereum & Co. Was zeichnet eine gute Kryptowährung aus? - N, N

Multiattributive elektronische Verhandlungen. Eine Anwendung des Adjusted Winner Verfahrens - N, N

Machtindizes in politischen Netzwerken - Eine spieltheoretische Analyse - N, N

Dynamische multikriterielle Lohnverhandlungen - N, N

Kooperative Standortspiele - N, N

Wie können Aufteilungsprobleme gelöst werden? Prozedurale Ansätze zur Konfliktlösung - N, N

Produkte und Dienstleistungen im Paket - Eine Analyse der strategischen Preissetzung - - N, N

Simultane bilatrale Verhandlungen - Die Zusammenstellung eines Sortiments - N, N

Netzwerkeffekte auf zweiseitigen Märkten - Eine ökonomische Betrachtung der Modelle - N, N

Optimale Projektverträge unter Kostenunsicherheit - N, N

How do differentiated goods affect coopetition? - N, N

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics, Peace Science and Public Policy)

Sustainability of coalitional equilibria within repeated tax competition - Brangewitz, Sonja; Brockhoff, Sarah (European Journal of Political Economy)

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Competition of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen (Theoretical Economics Letters)
On an intermediate goods market with asymmetric production technologies as well as vertical and horizontal product differentiation we analyze the influence of simultaneous competition for resources and customers. The intermediaries face either price or quantity competition on the output market and a monopolistic, strategically acting supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Moreover, the well-known welfare advantage of price competition can in general be no longer confirmed in our model with an endogenous input market and asymmetric intermediaries.

Competition in Markets with Intermediaries - Manegold, Jochen

Economic Aspects of Service Composition: Price Negotiations and Quality Investments - Brangewitz, Sonja; Hoof, Simon (Service-Oriented and Cloud Computing: 5th IFIP WG 2.14 European Conference, ESOCC 2016, Vienna, Austria, September 5-7, 2016, Proceedings)
We analyse the economic interaction on the market for composed services. Typically, as providers of composed services, intermediaries interact on the sales side with users and on the procurement side with providers of single services. Thus, in how far a user request can be met often crucially depends on the prices and qualities of the different single services used in the composition. We study an intermediary who purchases two complementary single services and combines them. The prices paid to the service providers are determined by simultaneous multilateral Nash bargaining between the intermediary and the respective service provider. By using a function with constant elasticity of substitution (CES) to determine the quality of the composed service, we allow for complementary as well as substitutable degrees of the providers' service qualities. We investigate quality investments of service providers and the corresponding evolution of the single service quality within a differential game framework.

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

Renegotiable vs. Non-Renegotiable Agreements - Theory and Applications - N, N

Wie wertvoll ist der Einzelne für das Team? - Performancemessung der Bundesligaspieler anhand der kooperativen Spieltheorie der Saison 2014/2015 - N, N

Automatisiertes Matching von Angebot und Nachfrage in der Kunststoffindustrie Ein Fallbeispiel in Kooperation mit der PINPOOLS GmbH - N, N

Der Einfluss von Netzwerken auf Gleichgewichtspreise - eine spieltheoretische Analyse - N, N

Hat vertikale Integration einen Einfluss auf die allgemeine Wohlfahrt? - N, N

Stabile Supply-Chains - Basierend auf der Theorie der Matching-Märkte - N, N

Die Berechnung von Machtindizes - ein Vergleich verschiedener Verfahren - N, N

Intermediaries in Buyer Seller Networks - N, N